A review of foodborne Toxoplasma gondii with a special focus on its prevalence in Pakistan from 2000 to 2022 - Qamar, Warda; Alsayeqh, Abdullah F. (Frontiers in Veterinary Science, 2023)
Third-world countries have a higher prevalence of food-related disorders than developed nations. Millions of people in underdeveloped countries are seriously at risk from the potential water supply contamination with protozoan diseases. Toxoplasma gondii is one of the important protozoans causing diseases in livestock and humans. Despite the standard tests for diagnosing this parasite and different treatment methods, the spread of these parasites is uncontrollable and rising every year due to other management disorders. In this review, we summarize etiopathogenesis and prevalence in Pakistan. We looked for papers reporting the seroprevalence of T. gondii in people and animals between 2000 and 2022 in different databases: PubMed, Google Scholar, ScienceDirect, Scopus, and Web of Science. Data on the seroprevalence of T. gondii in Pakistan's domestic animals (sheep and goats, horses, donkeys, mules, cattle, and buffaloes), domestic pets (cats, dogs), poultry and rodents, and humans were gathered. According to the findings, sheep had an estimated pooled seroprevalence of T. gondii that varied from 11.20 to 26.50 %, and goats from 24.50-38.40%. Whereas in buffalo the opposite trend was followed, and the prevalence was observed is 0% in 2022, in horses, donkeys, and mules, only one study was reported according to which a high prevalence was observed in mules (28.60%) followed by donkeys (23.50%) and horses (23.50%), in cats 38.5% prevalence was observed in a recent study and in dogs 28.43 % observed, and in humans from 22% to 60%. Human beings are found to be the most affected species showing high prevalence among all. According to our findings, animals and pets not only serve as a reservoir for the parasite but also serve as a direct route for human infection with T. gondii.The diagnostic techniques used in the observed studies were mostly serological testing whereas only a few studies have only been observed with molecular testing. To know the exact pattern of the disease for its control, the trend of molecular and advanced testing should be adopted as it is more reliable.Moreover, to decrease the transmission chances of T. gondii to humans, it is crucial to manage T. gondii infections in non-human species.